Investigating Immunization With Nucleotide Enzymes of Schistosoma mansoni: Nucleoside Diphosphate Kinase and Adenylosuccinate Lyase as New Antigenic Targets Against Schistosomiasis - Cagnazzo, Túlio di Orlando; Nogueira, Camila Tita; Castro, Cynthia Aparecida de; Neris, Débora Meira; Fattori, Ana Carolina Maragno; Correia, Ricardo de Oliveira; Albuquerque, Yulli Roxenne; Fragelli, Bruna Dias de Lima; Mendes, Tiago Manuel Fernandes; Allegretti, Silmara Marques; Soares, Edson Garcia; Romanello, Larissa; et al. (Frontiers in Immunology, 2020)
Schistosomiasis, caused by Schistosoma mansoni trematode worm, affects more than 1.5 million people in Brazil. The current treatment consists in the administration of Praziquantel, the only medicine used for treatment for more than 40 years. Some of the limitations of this drug consist in its inactivity against schistosomula and parasite eggs, the appearance of resistant strains and non-prevention against reinfection. Thus, the objective of this study was to evaluate the effect of immunization with recombinant functional enzymes of the purine salvage pathway of S. mansoni, Nucleoside Diphosphate Kinase (NDPK) and Adenylosuccinate Lyase (ADSL), to evaluate the host immune response, as well as the parasite load after vaccination. For this, Balb/c mice were divided into 5 groups: control (uninfected and untreated), non-immunized/infected, NDPK infected, ADSL infected and NDPK + ADSL infected. Immunized groups received three enzyme dosages, with a 15-day interval between each dose, and after 15 days of the last application the animals were infected with 80 cercariae of S. mansoni. On the 47th day after the infection, fecal eggs were counted and, on the 48th day after the infection, the evaluation of leukocyte response, parasite load, antibody production, cytokines quantification and histopathological analysis were performed. The results showed that immunizations with NDPK, ADSL or NDPK + ADSL promoted a discreet reduction in eosinophil counts in lavage of peritoneal cavity. All immunized animals showed increased production and secretion of IgG1, IgG2a and IgE antibodies. Increased production of IL-4 was observed in the group immunized with the combination of both enzymes (NDPK + ADSL). In addition, in all immunized groups there were reductions in egg counts in the liver and intestine, such as reductions in liver granulomas. Thus, we suggest that immunizations with these enzymes could contribute to the reduction of schistosomiasis transmission, besides being important in immunopathogenesis control of the disease.